Planning gain and the supply of new affordable housing in England: understanding the numbers. - Crook, A.; Monk, S.; Rowley, Steven; Whitehead, C. (Liverpool University Press, 2006)
The policy to generate land and finance for affordable housing through the land use planning system in England has now been in place for fifteen years – and is fast becoming the most important mechanism for adding to the stock of affordable housing. It is therefore an appropriate time to assess the extent to which the policy is achieving its objectives. To address this issue the paper draws on a number of complementary research projects to look at how the policy has developed and then at the evidence of outputs and outcomes. It first examines the numbers being achieved and the proportion of total output that this represents; it then looks at the regional and the tenure distribution of this output and lastly at the nature of other contributions made by developers. Finally the implications of the findings are discussed in the context of proposed policy changes